Islamic Education and Socio-Cultural Development in Educational Institutions - Firman Mansir (Ideas Publishing, 2022)
Religious and socio-cultural education is inseparable in peoples lives. Educational cultural proximity to religion and socio-cultural development become two interrelated and mutually needy sides in solving social problems of society. This research shows that there is a relationship between religious and cultural education that is interrelated, giving birth to changes and responding to the rapid development of the times, thus ushering in a reality of religious life that is full of educational values without losing the local culture. The success of a nation can be seen and measured by the younger generation of its nation in the present and the future. Regarding religious education with culture, it is hoped that there will be the best results from a new generation and have potential with good quality, who can develop the knowledge they have and apply it well in the fabric of education, society, and culture. Thus, religious and socio-cultural education provides answers to various problems in the social development of budaya to religion in the context of educational institutions, be it in schools or madrasas. Pendidikan Agama Islam dan sosial budaya tidak dapat dipisahkan dalam kehidupan masyarakat. Pendekatan kultural edukatif terhadap agama dan perkembangan sosial budaya menjadi dua sisi yang saling terkait dan saling membutuhkan dalam memecahkan persoalan sosial masyarakat. Penelitian ini menunjukkan bahwa terdapat hubungan antara pendidikan Agama Islam dan budaya yang saling berkaitan, dengan melahirkan perubahan serta merespon berkembangnya zaman yang semakin pesat, sehingga mengantarkan pada sebuah kenyataan kehidupan beragama yang sarat dengan nilai-nilai pendidikan tanpa menghilangkan budaya setempat. Berhasilnya suatu bangsa dapat dilihat serta diukur dari generasi muda bangsanya pada masa kini serta pada masa yang akan datang. Dalam hubungannya Pendidikan Agama Islam dengan budaya, sangat diharapkan adanya hasil terbaik dari generasi yang baru dan memiliki potensi dengan kualitas yang baik, yang mampu untuk mengembangkan ilmu pengetahuan yang dimiliki dan mengaplikasikannya dengan baik dalam jalinan pendidikan, sosial dan budaya. Dengan demikian, Pendidikan Agama Islam dan sosial budaya memberi jawaban dari berbagai permasalahan dalam perkembangan sosial budaya terhadap agama dalam konteks lembaga pendidikan, baik itu di sekolah maupun madrasah.